Gadolinium chloride modulates bradykinin-induced pulmonary vasoconstriction and hypoxic pulmonary vasoconstriction during polymicrobial abdominal sepsis in rats. (1st June 2015) - Lauer, Stefan; Fischer, Lars G; Van Aken, Hugo K; Nofer, Jerzy-Roch; Freise, Hendrik
ABSTRACT Background: Macrophages importantly contribute to sepsis-induced lung injury. As their impact on pulmonary endothelial injury and dysregulation of hypoxic pulmonary vasoconstriction (HPV) remains unclear, we assessed pulmonary endothelial dysfunction and HPV by macrophage inhibition via gadolinium chloride (GC) pre-treatment in rats with peritonitis (cecal ligation and puncture [CLP]). Methods: The following four study groups were made: Group I: SHAM and group II: SHAM + GC (pre-treatment with NaCl 0.9% or GC 14 mg/kg body weight (b.w.) intravenously 24 hours prior to sham laparotomy); group III: CLP and group IV: CLP + GC (pre-treatment with NaCl 0.9% or GC 14 mg/kg b.w. 24 hours prior to induction of peritonitis). Exhaled nitric oxide (exNO), bradykinin-induced pulmonary vasoconstriction (=surrogate marker of endothelial dysfunction) and HPV were investigated in isolated and perfused lungs (n = 40). Using the same protocol wet to dry lung weight ratio and myeloperoxidase (MPO) activity were investigated in separate rats (n = 28). In additional rats (n = 12) of groups III and IV nitrite levels in alveolar macrophages (AM) were measured. Results: In sepsis, GC pre-treatment significantly attenuated exNO levels, AM-derived nitrite levels, lung MPO activity, and restored blunted HPV, but severely enhanced endothelial dysfunction in healthy and septic animals. Conclusion: Macrophages exhibit a controversial role in sepsis-induced lung injury. The GC-induced restoration of inflammation parameters to sham levels is clearly limited by the negative impact on CLP-induced endothelial injury in this setting. The exact link between the GC-associated modulation of the NO pathway demonstrated and septic lung injury needs to be determined in future studies.